Founder of Hasidism a quest for the historical Ba'al Shem Tov - Rosman, Moshe 1949- (The Littman Library of Jewish Civilization, 2014)
Moshe Rosman's award-winning research supplies the history behind the legend of the Ba'al Shem Tov and thus changes the master-narrative of hasidism
Originally published in 2013. - Title from publisher's bibliographic system (viewed on 05 Jul 2019)
Keywords: Baʻal Shem Ṭov / approximately 1700-1760; Yisraʾel ben Eliʿezer Baʿal Shem Ṭov -- 1700-1760; Hasidim / Ukraine / Biography; Rabbis / Ukraine / Biography; Hasidism / History / 18th century; Biografie